1999
DOI: 10.1054/jhsb.1999.0236
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dominant and Non-Dominant Hand Strengths

Abstract: This study compares dominant and non-dominant hand strength in both right- and left-handed participants. Maximum voluntary contraction (MVC) of the first dorsal interosseous (FDI) muscle, power grip strength and pulp-to-pulp pinch strength were assessed under carefully controlled conditions. No significant differences were observed between dominant and non-dominant hands in left-handed participants for all tests. Small but significant differences (0.1-3%) were observed between dominant and non-dominant hands i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
115
4
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(140 citation statements)
references
References 11 publications
15
115
4
6
Order By: Relevance
“…The six studies pooled for grip strength 13,14,18,[31][32][33] showed a large variability, and none of the studies could be identified as causing major heterogeneity. Several authors have reported considerable variability in the relative strength of the two hands in a healthy population, and grip strength has been shown to be typically greater on the dominant side than on the nondominant side [36][37][38] . Therefore, the rate of dominant-hand injury, ranging from 34% to 64% across the five studies, could account for some of the grip strength variability among studies.…”
Section: Key Findingsmentioning
confidence: 99%
“…The six studies pooled for grip strength 13,14,18,[31][32][33] showed a large variability, and none of the studies could be identified as causing major heterogeneity. Several authors have reported considerable variability in the relative strength of the two hands in a healthy population, and grip strength has been shown to be typically greater on the dominant side than on the nondominant side [36][37][38] . Therefore, the rate of dominant-hand injury, ranging from 34% to 64% across the five studies, could account for some of the grip strength variability among studies.…”
Section: Key Findingsmentioning
confidence: 99%
“…Our data from dexterity testing with NHPT showed that the dominant hand completed test faster compared to non -dominant hand in both the trunk orientation. The superior performance of dominant hand over nondominant hand has been attributed to hemispheric lateralization12 contradictory finding of Hage JJ reported that there was no difference between dominant and non-dominant hands [13]. Result of this study was favoured by the finding of Armstrong and Oldham observed small but significant differences between the dominant and non-dominant hands [14].…”
Section: Discussionmentioning
confidence: 70%
“…right-handers predominantly show a distinct superiority of the preferred hand (5,10,29). But also low differences were found for hGs between 5-8% (10) or <5% or none (1). for left-handers considerably smaller differences between the preferred and supporting hand were found, or no asymmetry (11).…”
Section: Introductionmentioning
confidence: 89%